Chronic effects of a training program using a nasal inspiratory restriction device on elite cyclists - Gonzalez-Montesinos, J. L.; Fernandez-Santos, J. R.; Vaz-Pardal, C.; Aragon-Martin, R.; Arnedillo-Muñoz, A.; Reina-Novo, J.; Orantes-Gonzalez, E.; Heredia-Jimenez, J.; Ponce-Gonzalez, J. G. (International Journal of Environmental Research and Public Health, 2021)
This study compared the response of a 9-week cycling training on ventilatory efficiency under two conditions: (i) Combined with respiratory muscle training (RMT) using a new nasal restriction device (FeelBreathe) (FB group) and (ii) without RMT (Control group). Eighteen healthy elite cyclists were randomly separated into the FB group (n = 10) or Control group (n = 8). Gas exchange was measured breath by breath to measure ventilatory efficiency during an incremental test on a cycloergometer before (Pre) and after (Post) the nine weeks of training. The FB group showed higher peak power (? (95%HDI) (0.82 W/kg (0.49, 1.17)), VO2max (5.27 mL/kg/min (0.69, 10.83)) and VT1 (29.3 W (1.8, 56.7)) compared to Control at PostFINAL. The FB group showed lower values from Pre to PostPRE in minute ventilation (VE) (-21.0 L/min (-29.7, -11.5)), Breathing frequency (BF) (-5.1 breaths/min (-9.4, -0.9)), carbon dioxide output (VCO2) (-0.5 L/min (-0.7, -0.2)), respiratory equivalents for oxygen (EqO2) (-0.8 L/min (-2.4, 0.8)), heart rate (HR) (-5.9 beats/min (-9.2, -2.5)), respiratory exchange ratio (RER) (-0.1 (-0.1, -0.0) and a higher value in inspiratory time (Tin) (0.05 s (0.00, 0.10)), expiratory time (Tex) (0.11 s (0.05, 0.17)) and end-tidal partial pressure of CO2 (PETCO2) (0.3 mmHg (0.1, 0.6)). In conclusion, RMT using FB seems to be a new and easy alternative ergogenic tool which can be used at the same time as day-to-day training for performance enhancement.